Dampak Perubahan Iklim terhadap Ekosistem Hutan Tropis di Indonesia - Fita Kharisma Ameliyah; Elsa Kamila Iskandar; Nurhayyizah Nurhayyizah; Ade Suryanda (Biocaster : Jurnal Kajian Biologi, 2025)
Climate change is a global problem characterized by increasing temperatures and environmental instability due to human activities, such as the use of fossil fuels and deforestation. This study aims to analyze the impact of climate change on tropical forests and provide scientific insights for effective mitigation. Qualitative descriptive methods were used with literature studies from journals, books, and other academic references. The results showed a significant increase in temperature in the tropical forests of East Kalimantan, reaching 0.95°C per decade, which disrupts the ecosystem, increases the risk of fire, and changes rainfall patterns. These changes, triggered by greenhouse gas emissions and decreased forest cover, exacerbate global warming and biodiversity loss. Mitigation efforts include reforestation, sustainable forest management, and international collaboration through the REDD+ program. These results emphasize the importance of forest conservation as a primary strategy for climate action.